Foreign capital as an instrument of national economic policy : a study based on the experience of East European countries between the world wars - Bandera, V. N. (The Hague : M. Nijhoff, 1964)
This book examines the task of rehabilitating the underprivileged countries. This study of a closed chapter in the history of six East European countries was undertaken with the intention of shedding some light on a question with which our century will remain preoccupied: what role can be assigned to international capital movements to promote economic stability and development.
Bibliography: p. [145]-150.
usc 04/10/18
Loans
Keywords: Investments, Foreign; Production management; Business; Economic policy; Economics; Europe, Eastern